Anesthesia of fish with benzocaine does not interfere with comet assay results - De Miranda Cabral Gontijo, Álisson Marques [UNESP]; Barreto, Rodrigo Egydio; Speit, Günter; Valenzuela Reyes, Victor Alexis [UNESP]; Volpato, Gilson Luiz; Salvadori, Daisy Maria Favero [UNESP] (Elsevier, 2003)
Fish blood erythrocytes are frequently used as sentinels in biomonitoring studies. Usually, fish blood is collected by painful cardiac or caudal vein punctures. Previous anesthesia could decrease animal suffering but it is not known at present whether anesthesia can cause confounding effects. Therefore, using the alkaline single cell gel (SCG)/comet assay with blood erythrocytes of the cichlid fish Nile tilapia, we tested for a possible modulation of induced DNA damage (methyl methanesulfonate; MMS) by the anesthetic benzocaine administered by bath exposure (80mg/l for ∼10min). Furthermore, benzocaine (80-600mg/l) was tested for its genotoxic potential on fish erythrocytes in vitro and for potential interactions with two known genotoxins (MMS and hydrogen peroxide). Our results did neither indicate a significant increase in the amount of DNA damage (even after a 48h follow-up), nor indicated interactions with MMS-induced DNA damage when fish were exposed to benzocaine in vivo. There was also no increase in DNA damage after in vitro exposure of fish erythrocytes to benzocaine. Clear concentration-related effects were observed for the two genotoxins in vitro, which were not significantly altered by the presence of benzocaine. These results suggest that anesthesia of fish does not confound comet assay results and the use of blood samples from anesthetized fish can be recommended with regard to animal welfare. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Anesthetic benzocaine (ethyl p-aminobenzoate); Animal welfare; DNA damage; Fish; Nile tilapia; Single cell gel (SCG)/comet assay; benzocaine; hydrogen peroxide; mesylic acid methyl ester; toxin; anesthesia; animal welfare; biological monitoring; blood sampling; comet assay; concentration response; controlled study; erythrocyte; fish; in vitro study; modulation; nonhuman; priority journal; Tilapia; vein puncture; Alkylating Agents; Anesthetics, Local; Animals; Benzocaine; Comet Assay; Erythrocytes; Hydrogen Peroxide; Methyl Methanesulfonate; Animalia; Cichlidae; Oreochromis niloticus